Electron ionization mass spectra of phosphorus-containing heterocycles. I. 1,4,4a,5,6,7,8,8a-octahydro-2H-3,1,2-benzoxazaphosphinine 2-oxides - Juhász, Márta; Martiskainen, Olli; Zalán, Zita; Fülöp, Ferenc; Pihlaja, Kalevi (Rapid communications in mass spectrometry, 2006)
The electron ionization mass spectra of 27 cis‐ and trans‐annelated 1,4,4a,5,6,7,8,8a‐octahydro‐2H‐3,1,2‐benzoxazaphosphinine 2‐oxides were recorded to clarify the effects of the ring heteroatom (O or N), ring annelation, the P configuration and the substituents attached to the ring or to the N and P atoms. For compounds 1–12 different alkyl radical and alkene losses and the cleavage of the P–heteroatom bonds, instead of the P–C bonds, were representative and dependent mainly on the substitution on the N and P atoms. The replacement of Ph and OPh by N(CH2CH2Cl)2 on the P atom had a dramatic influence on the fragmentation process: new fragment ions were obtained and very little M+. (1–3%) was formed. Only slight differences were found between some of the corresponding isomers, but interestingly the compounds formed clear groups on the basis of the differences in their fragmentation, depending on the ring‐N and ring‐P substituents. Copyright © 2006 John Wiley & Sons, Ltd.